A nomogram based on clinical factors for preoperative prediction of nipple involvement in breast cancer - Huang, Weiling; Qiu, Zhikun; Mu, Tai; Li, Xi (Frontiers in Surgery, 2022)
Background. At present, the indication for nipple-sparing mastectomy (NSM) remains inconclusive, and occult Nipple involvement (NI) is one of the most considerable problems when carrying out NSM. We aimed to identify the predictive factors of NI, to provide an implement of selecting suitable candidates for NSM. Methods. In this retrospective study, a total of 250 breast cancer patients who received mastectomy were recruited, and the association between NI and tumor clinicopathologic characteristics was investigated. The nipple signs, tumor size measured by ultrasound (US) and tumor location were developed as a nomogram to predict the NI. Results. Among the 250 patients, 34(12.6%) had NI, 216(86.4%) did not. In the training group, NI was associated with nipple signs, tumor size, tumor-nipple distance (TND), tumor location, lymph node metastasis, and HER2 overexpression. Both in the training and validation groups, NI showed significant association with nipple signs, tumor size measured by ultrasound, and tumor location. Based on the three clinical factors, the preoperative model nomogram was proved to have high efficiency in predicting NI, possessing sensitivity of 80.0% and specificity of 86.7% in the validation group. Conclusions. We proposed a predictive model nomogram utilizing preoperative tumor characteristics, including nipple signs, tumor size measured by ultrasound, and tumor location. This predictive model could help in the planning of nipple-sparing mastectomy. Keywords: Nipple-sparing mastectomy, Nipple involvement, Predictive factors.